INHERITANCE RIGHTS OF OUTSIDE MARRIAGE DESCENDANTS AFTER THE RULING OF THE CONSTITUTIONAL COURT NUMBER 46 OF 2010 - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Ongko , Eric; Wibowo, Stefani; Kamal, Julius (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Humans were created by God to consist of men and women, therefore they are required to live in pairs in a bond called marriage. As stated in the 1945 Constitution, Article 28B Paragraph (1), which reads